Ecological Human Resource Management System: A Proposed Model that Enhances Corporate Environmental Responsibility by Supporting Citizenship Behavior - Suba , M. (International Journal of Psychosocial Rehabilitation, 2020)
A lot of articles have explained the importance of eco-friendly personal administration and its practices. With the previous view, the researcher studied the relationship between some of the organizational green elements and firms organizational corporate environmental responsibility. "The green management is a part of corporate environmental responsibility" the research was conducted to test the above statement and to find the actual link between this factors 100 samples were collected and analyzed. SPSS statistical package was used to represents the result. Correlation and regression analysis tools have been used to find the relationship between the two factors.